Teaching digital competences: a rural teaching perspective - Fernández Miranda, Marina; Jurado Rosas, Adolfo Antenor (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The COVID-19 pandemic has posed challenges, where ICT has become a basic need for humanity, in this context the capacities of teachers to face changes were questioned. It has a mixed pre-experimental methodology, 49 teachers participated and a questionnaire, rubric and Pre-Test/Post Test were applied, with values of 0.890; 0.91, Cronbach’s 0.97. The findings showed that the dimensions, communication, content creation, were very high, while the security and problem-solving dimension turned out to be good. The research obtained significant results for the development of digital skills of teachers in Piura.